2014
DOI: 10.1007/s00216-014-8043-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of deamidation artifacts induced by microwave-assisted tryptic digestion of a monoclonal antibody

Abstract: The thorough characterization of biopharmaceuticals is essential for ensuring their quality and safety since many potential variations can cause changes to the properties of a drug that may be detrimental to the patient such as decreased efficacy, shorter half-life or increased immunogenicity. Prior to approval and release, protein-based drugs are subject to a battery of analyses to assess the nature of those parameters that are considered critical quality attributes. In some cases the analytical method used m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Artificial deamidation from tryptic digestion facilitated by high temperature and long digestion time at basic pH has been widely reported. [9][10][11]31,32 After decreasing the digestion time of anti-CRTh2 from 3 h at 37 °C to 1 h at room temperature, we observed a significant decrease in artificial deamidation. By searching for the overall intensities of the peptides as well as uncleaved proteins, we observed that digestion efficiency was high when sufficient denaturant (8 M urea) and tryptic enzyme (1:10 w/w ratio) were used (results not shown).…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…Artificial deamidation from tryptic digestion facilitated by high temperature and long digestion time at basic pH has been widely reported. [9][10][11]31,32 After decreasing the digestion time of anti-CRTh2 from 3 h at 37 °C to 1 h at room temperature, we observed a significant decrease in artificial deamidation. By searching for the overall intensities of the peptides as well as uncleaved proteins, we observed that digestion efficiency was high when sufficient denaturant (8 M urea) and tryptic enzyme (1:10 w/w ratio) were used (results not shown).…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…This indicates that tryptic digestion of proteins can be improved. Based on recent studies [ 74 , 75 ], we believe that increasing the digestion time from 15 to 60 min at 50°C can be our next immediate improvement. In addition to increasing the number of CIPs, better tryptic digestion reduces the occurrences of missed cleavages, allowing the analyses to be done with a smaller allowed MCS.…”
Section: Discussionmentioning
confidence: 99%